New species of Demosthenesia (Ericaceae) from Cusco, Perú - Huamantupa Chuquimaco, Isau (2008)
A new species of Demosthenesia (Ericaceae) is described, from San Antonio, La Convención Valley, Cusco Department: Demosthenesia matsiguenka I. Huamantupa. It is compared to D. vilcabambensis Luteyn.